Redescription and lectotype designation of the species Eutrombicula alfreddugesi (Oudemans, 1910) (Trombidiformes: Trombiculidae) - Bassini-Silva, Ricardo [UNESP]; Welbourn, Cal; Ochoa, Ronald; Barros-Battesti, Darci Moraes [UNESP]; de Castro Jacinavicius, Fernando (Taylor & Francis, 2024)
Eutrombicula alfreddugesi (Oudemans, 1910) is the most common chigger parasitic on humans and widely distributed throughout the Americas. Examination of the type specimens revealed differences from those of the original description and subsequent redescriptions. A detailed redescription based on an examination of the type specimens of E. alfreddugesi is provided and illustrated with micrographs to aid in identification, as well as designating a lectotype and a paralectotype for this species. The distribution of E. alfreddugesi may be much more restricted than what has been reported in the literature.
Keywords: Acari; Chigger; collection; ectoparasite; types